Characteristics of Surian Flower, Fruit and Seed Productions (Toona sinensis (A. Juss.) M. Roem.) in Sumedang, West Java - Agus Astho Pramono; Endah Retno Palupi; Iskandar Zulkarnaen Siregar; Cecep Kusmana (Tropical Life Sciences Research, 2016)
Community forest development requires a constant supply of high-quality seeds. In addition, sound management of Toona sinensis (surian) seed sources requires a deep understanding of factors affecting seed production. This present study investigated the reproduction characteristics of surian, including flower, fruit and seed productions, variations in the productions of fruits and seeds among trees and among branches, and dendrometric factors that influence the productions of fruits and seeds. Flower production characteristics were observed in 99 panicles, fruit production characteristics were observed in 128 panicles, and seed characteristics were evaluated based on 890 fruits. The number of fruits per panicle ranged from 38 to 646. The number of seeds in fruits ranged from 1 to 35. Fruit size was correlated to the number of filled seeds following a quadratic regression equation. The optimal number of filled seeds was 20 per fruit. Stem diameter, crown width, crown base height, and the number of sub-branches positively influenced the production of panicles per tree, while the crown base height (of the tree) negatively affected the fruit set. Pembangunan hutan rakyat memerlukan bekalan tetap benih berkualiti tinggi. Selain itu, pengurusan sumber benih Toona sinensis (surian) yang baik memerlukan pemahaman mendalam tentang faktor-faktor yang mempengaruhi pengeluaran. Kajian ini terutamanya bertujuan untuk mengetahui ciri-ciri pembiakan yang meliputi ciri-ciri pengeluaran bunga, buah dan benih surian, variasi pengeluaran buah dan biji antara pohon-pohon dan di antara cabang-cabang, dan faktor dendrometrik yang mempengaruhi pengeluaran buah dan benih. Pemerhatian ciri-ciri pengeluaran bunga dilakukan pada 99 bulir, ciri-ciri pengeluaran buah diperhatikan pada 128 bulir, dan ciri-ciri benih dinilai berdasarkan 890 buah. Jumlah buah per bulir berkisar antara 38 hingga 646. Bilangan biji dalam buah berjulat antara 1 hingga 35. Saiz buah berkaitan dengan jumlah biji berisi mengikuti persamaan regresi kuasa dua. Jumlah optimum benih berisi adalah 20 per buah. Diameter batang, lebar silara, tinggi dasar silara, dan jumlah sub-cabang berpengaruh positif terhadap pengeluaran bulir per pohon manakala ketinggian dasar silara (pokok) berpengaruh negatif terhadap pembentukan buah.